Challenges in requirements engineering for e-learning elicitation process / Noorihan Abdul Rahman and Shamsul Sahibuddin - Abdul Rahman, Noorihan; Sahibuddin, Shamsul (Unit Penerbitan UiTM Kelantan, 2016)
Requirement Engineering (RE) is a crucial phase in software development process. It is a process to allow users and developers to elicit required information during requirements gathering before implementation starts. Collaborative application is an example of software that possesses knowledge sharing as the main component needed by users in using the application. RE supports software implementation by identifying requirements specification needed for supporting knowledge sharing. This paper gives an overview of requirements elicitation in collaborative application under the umbrella of RE. Thus, Electronic learning domain will be used as an example of collaborative application in order to give the idea of knowledge sharing among users. Electronic-learning can be seen as a collaboration of entities which comprises students, instructors, administrators, designers and developers of the application. Therefore, the challenges of E-learning are also highlighted in this paper in order to depict the importance of RE process for software development purpose